2023
DOI: 10.1186/s12870-023-04338-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the chloroplast genomes of Rosa species and RNA editing analysis

Abstract: Background The genus Rosa (Rosaceae) contains approximately 200 species, most of which have high ecological and economic values. Chloroplast genome sequences are important for studying species differentiation, phylogeny, and RNA editing. Results In this study, the chloroplast genomes of three Rosa species, Rosa hybrida, Rosa acicularis, and Rosa rubiginosa, were assembled and compared with other reported Rosa chloroplast genomes. To investigate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…The length of the seven chloroplast genomes was 156,544 bp, the number of genes was approximately 130, and the GC content was approximately 37.24%. These data closely resemble reports from other sections of the Rosa genus [31][32][33], suggesting that Rosa species share low diversity. The contraction and expansion of IR regions are the main driving forces of chloroplast genome structure variation in some taxa [34].…”
Section: Discussionsupporting
confidence: 86%
“…The length of the seven chloroplast genomes was 156,544 bp, the number of genes was approximately 130, and the GC content was approximately 37.24%. These data closely resemble reports from other sections of the Rosa genus [31][32][33], suggesting that Rosa species share low diversity. The contraction and expansion of IR regions are the main driving forces of chloroplast genome structure variation in some taxa [34].…”
Section: Discussionsupporting
confidence: 86%
“…RNA editing is a posttranscriptional modification process that encompasses an indel or the conversion of cytidine (C) to uridine (U) nucleic acid bases within the plastids of angiosperms [19] . In this study, it was observed that the ycf1 gene exhibited the highest number of editing sites among the plastid genomes of the Hydrangeaceae family ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the evolution of mitochondrial genomes has been characterized by many intergenomic sequence transfers and structural rearrangements (Wu et al. ; Allen, 2015 ; Gao et al., 2023 ). At the same time, mitochondrial protein-coding genes are conserved, hence a potential for addressing unresolved phylogenetic questions ( Tian et al., 2006 ; Hao et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%